Exploring shopping travel behavior of millennials in Beijing: Impacts of built environment, life stages, and subjective preferences. (May 2021) - Zhang, Yixue; Zhao, Pengjun; Lin, Jen-Jia
Highlights: Millennials make their mode choices of shopping travel based on built-environment, socio-economic status, and preferences. Completed shopping facilities around neighborhoods encourage active modes. Millennials with different life stages and shopping habits have differentiated preferences on mode choice. To encourage non-motorized travel modes, neighborhood design should consider socio-economic attributes of its residents. Abstract: China's cities have witnessed rapid growth of the consumption economy in recent years. The millennials (defined in this study as those born between 1980 and 2000, also known as Generation Y) have become one of the main forces of domestic consumption. Thus, shopping trips of millennials significantly influence the transportation sector in the context of the consumption society. Previous studies intensively investigated the determinants of non-work travel. However, only a few empirical analyses were conducted on the shopping travel behavior of millennials in China's cities. In addition, few studies integrated the influence of life stages and shopping habits in their analysis of travel behavior. The purpose of the study is to fill these research gaps by taking Beijing as a case. By using travel survey data in Beijing, this study explores the characteristics and determinants of shopping travel by millennials. A multinomial logistic (MNL) model is applied to investigate the travel mode choice of millennials for shopping purposes. A latent class (LC) model is used to further specify segment preferences according to individual life stages and shopping habits. The impacts of several major factors are addressed. These factors include neighborhood built environments, individual subjective attitudes toward travel, and household attributes. Results show that the completed commercial facilities and public transportation connections surrounding the neighborhoods would encourage shopping by walking or cycling. The findings and conclusions could enhance the knowledge of millennials' travel behavior and contribute to policy-making to encourage sustainable transport by integrating land use and transportation planning strategies.